Analysis of the Influence Characteristics of the Support Stability of a Fully Mechanized Coal Mining Face under the Hard Roof Mining Pressure - Jiaxin Dang (Hindawi Limited, 2021)
The conditions of the hard roof in my country vary greatly, ranging from a few meters to tens of meters or even hundreds of meters in thickness. The coal reserves under the hard roof account for about one-third of the total reserves. At present, nearly 40% of fully mechanized mining faces that belong to the hard roof working face has the problem of mining in the hard roof working face. This has a serious impact on the load-bearing stability of the fully mechanized support, and it is urgent to solve the problem of strong underground pressure dynamic disaster under the condition of the hard roof. Based on the research background of 11129 working face in Zhangji Coal Mine in Huainan, this paper constructs a mechanical model of the interaction between the cantilever beam of the hard roof of the stope and the support and then the force distribution equation of the bearing capacity of the supports at different positions of the roof during the periodical rotation of the working face is obtained, which is combined with numerical simulation and engineering site to verify. The research results show that the bearing stability of the support is significantly affected by factors such as the buried depth H, the roof elastic modulus E, the roof thickness h, and the roof cantilever length l0, but most of the influencing factors belong to the geological occurrence conditions of the coal seam itself. Presplit blasting of the roof in advance can effectively destroy the integrity of the roof itself and reduce the periodic breaking distance, thereby improving the apparent environment of roof rock pressure and reducing the force on the working face support. According to the specific geological environment of the 11129 working face, the cutting plan of the cut hole is given out, along the groove 0∼200 and 200∼700 m of the concrete presplitting blasting. The stent force of the top-cutting section fluctuates in the range of 3360.8–4347.9 kN in the range of control top distance (5275∼6175 mm). The load-bearing pressure of the stent before top-cutting is about 1.8 times of that after top-cutting. The pressure distribution of the hydraulic support in the numerical simulation stope is approximately “Λ” in the middle and the low on the two sides. The simulated value is slightly smaller than the theoretical calculation value. The reason is that the goaf is backfilled during the simulation process, and the roof has a certain ability to bear the load. Real-time understanding of the “roof-support” mechanical relationship can effectively ensure the safe and efficient mining of the 11129 working face and also provide experience for the subsequent mining of group B coal in the later period.